Efektivitas Taman Kota 1 BSD Sebagai Ruang Terbuka Hijau Publik Di Kawasan Perkotaan BSD City, Kota Tangerang Selatan - Wildan Fadhlillah Ardi; Parfi Khadiyanto (Ruang, 2017)
City Park 1 BSD is open spaces seeded owned by urban area BSD city and also south tangerang to realize the smart city concept through smart environtment aspect.But the number of visitors has exceeded capacity city parks, physical condition are unmaintained, and loss of function a means to educate on city park has been a problem that causes City Park 1 BSD to be less effective.This research used the quantitative descriptive with the help of Likert Scale on the analysis to get score of effectiveness by partial and overall Results from this study is the value of the effectiveness of City Parks 1 BSD that viewed as a partial, characteristic of visitors criteria, characteristic of physical condition criteria, criteria function, the public nature open space, and criteria management  areeffective.The total value of the effectiveness of city parks 1 bsd as green space public in urban areas BSD City is quite effective with value 71,712. Decent condition effective the does not mean that all indicators used in analysis is in good condition but indicators, had some a problem so that the indicators has been available and walks but it is not maximal.